Investigating the insulin-like growth factor axis in head and neck cancer - Dale, Oliver (2016)
Head and neck squamous cell carcinoma (HNSCC) is the sixth commonest cancer in the UK. Despite recent therapeutic developments, survival rates remain poor, particularly in advanced cancer and Human Papilloma Virus (HPV) negative disease. Novel treatments approaches are therefore urgently required. The type-1 insulin-like growth factor receptor (IGF-1R) regulates cellular growth and survival and is over-expressed in a range of cancer types. Other groups reported that inhibition of IGF-1R reduces HNSCC cell survival and sensitises to ionising radiation, but a clinical trial of IGF-1R inhibition as monotherapy was inactive in unselected palliative patients with HNSCC. These data suggest that predictive biomarkers for response to IGF-1R inhibition are required.